2018
DOI: 10.3390/md16090312
|View full text |Cite
|
Sign up to set email alerts
|

Aspergixanthones I–K, New Anti-Vibrio Prenylxanthones from the Marine-Derived Fungus Aspergillus sp. ZA-01

Abstract: Marine-derived fungi are a rich source of structurally diverse metabolites. Fungi produce an array of compounds when grown under different cultivation conditions. In the present work, different media were used to cultivate the fungus Aspergillus sp. ZA-01, which was previously studied for the production of bioactive compounds, and three new prenylxanthone derivatives, aspergixanthones I–K (1–3), and four known analogues (4–7) were obtained. The absolute configuration of 1 was assigned by ECD experiment and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 20 publications
0
29
0
1
Order By: Relevance
“…Asperxanthone, a difuraxanthone reported from marine-derived Aspergillus species exhibited moderate activity against tobacco mosaic virus (Wu et al, 2009). Some prenylxanthone analogs with various bioactive functions such as antibacterial, antifungal and cytotoxic activities have been reported from the Aspergillus species (Zhu et al, 2018). Butylidenephthalide, present in many medicinal herbs possesses various bioactivities including antitumor activity (Chang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Asperxanthone, a difuraxanthone reported from marine-derived Aspergillus species exhibited moderate activity against tobacco mosaic virus (Wu et al, 2009). Some prenylxanthone analogs with various bioactive functions such as antibacterial, antifungal and cytotoxic activities have been reported from the Aspergillus species (Zhu et al, 2018). Butylidenephthalide, present in many medicinal herbs possesses various bioactivities including antitumor activity (Chang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…When the coupling constant of H-19b and H-20 is small, it is suggested that isopropenyl group is pseudo-axial oriented and the OH-25 group and the isopropenyl group therefore possesses anti stereochemistry. Examples of this kind of situation included shamixanthone ( J H19b–H20 = 2.8 Hz) [10], tajixanthone derivatives ( J H19b–H20 = 2.8 Hz) [12], and aspergixanthones J–K ( J H19b–H20 = 3.0 Hz) [14]. Conversely, if the coupling constant of H-19b and H-20 is a large value, the isopropenyl group on C-20 is oriented equatorial and it means that OH-25 and the isopropenyl group has a syn relationship, such as epitajixanthone hydrate ( J H19b–H20 = 11.8 Hz) [12], aspergixanthone I ( J H19b–H20 = 12.0 Hz) [14], and epishamixanthone ( J H19b–H20 = 11.0 Hz) [16].…”
Section: Resultsmentioning
confidence: 99%
“…Examples of this kind of situation included shamixanthone ( J H19b–H20 = 2.8 Hz) [10], tajixanthone derivatives ( J H19b–H20 = 2.8 Hz) [12], and aspergixanthones J–K ( J H19b–H20 = 3.0 Hz) [14]. Conversely, if the coupling constant of H-19b and H-20 is a large value, the isopropenyl group on C-20 is oriented equatorial and it means that OH-25 and the isopropenyl group has a syn relationship, such as epitajixanthone hydrate ( J H19b–H20 = 11.8 Hz) [12], aspergixanthone I ( J H19b–H20 = 12.0 Hz) [14], and epishamixanthone ( J H19b–H20 = 11.0 Hz) [16]. In this study, the pattern of the coupling constants of compound 1 was in accordance with the relevant characteristics of previously reported related compounds, and the large coupling constant of H-19b and H-20 ( J = 11.0 Hz) indicated a syn relationship.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations